P16.06 Immunophenotyping of tumor-infiltrating T cells in primary CNS lymphoma. (9th September 2021) - Schliffke, S; Maire, C; Holz, M; Bokemeyer, C; Westphal, M; Lamszus, K; Mohme, M
Abstract: BACKGROUND: Primary CNS lymphoma represents a malignant disease with dismal prognosis. Standard of care is high dose chemotherapy and radiation. However, this combination cannot be applied to the elderly and fragile population. Immunotherapy holds great promise to be effective in these patients. This study therefore aims to explore the phenotype of tumor-infiltrating lymphocytes (TIL) in order to analyze the potential for immune checkpoint inhibition. MATERIAL AND METHODS: We performed ex vivo multicolor flow-cytometry on surgical specimens of nine patients with intracerebral lymphoma, including seven with primary CNS lymphoma after isolation of TILs following standard protocols. Data was analyzed using a Fortessa LSR flow cytometer and Diva software. The study was approved by the local ethics committee (PV4904). RESULTS: Our ex vivo phenotyping demonstrated a predominant infiltration of CD8+ T cells, which outnumber CD4+ T cells by a ratio of 2:1 (p<0.01). Regulatory T cells (Tregs) were not increased in the tumor microenvironment and the NK cell frequency was reduced compared to the peripheral blood. While CD4+ T helper cells displayed significantly increased surface expression of multiple activation and checkpoint markers, including TIGIT, PD-1, Tim3 and CD57, cytotoxic CD8+ T cells predominantly expressed only TIGIT and PD-1. On average 70% and 80% of CD8+ T cells expressed PD-1 and TIGIT, respectively, compared to 35% and 60% of PD-1 and TIGIT on CD4+ T cells (p<0.05). CD8+ T cells furthermore showed an increased expression of CD39 and a simultaneous downregulation of CD73, both ectoenzyms involved in the modulation of intratumoral ATP, thereby indicating a metabolic immune modulation by the tumor. CONCLUSION: Taken together, our study demonstrates a strong infiltration of cytotoxic CD8+ T cells into cerebral lymphoma, which potentially can be disinhibited using checkpoint immunotherapy. Our profiling suggests that PD-1 and TIGIT present appealing targets for such kind of immune disinhibition.